2019
DOI: 10.3390/nu11020303
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Liver Steatosis in Patients with Inflammatory Bowel Diseases

Abstract: Background and Aim: Most studies focused on the benefits of weight loss on hepatic steatosis and no studies have been specifically designed to assess the role of weight gain on the development of liver steatosis in patients affected by inflammatory bowel diseases. The aim of this study was to analyse the relation between weight change over time and liver steatosis in patients with inflammatory bowel diseases. Methods: We retrospectively evaluated a population of 89 ambulatory patients in clinical remission or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…This could be a direct effect of the aggressive medical therapy currently available, and represents a warning regarding the future management of obesity in younger populations. Persistent remission of disease is the main factor linked to weight gain, more so than medications, which were not significantly responsible for this metabolic profile [ 26 ]. McGowan et al identified the improvement of therapies and nutritional status as being a cause of increased BMI among patients affected by quiescent Crohn’s disease, with there being a direct relationship between prolonged remission, higher risk of MetS, and development of NAFLD [ 21 ].…”
Section: Nafld In Ibd Patients With “Metabolic Syndrome Profile”mentioning
confidence: 99%
“…This could be a direct effect of the aggressive medical therapy currently available, and represents a warning regarding the future management of obesity in younger populations. Persistent remission of disease is the main factor linked to weight gain, more so than medications, which were not significantly responsible for this metabolic profile [ 26 ]. McGowan et al identified the improvement of therapies and nutritional status as being a cause of increased BMI among patients affected by quiescent Crohn’s disease, with there being a direct relationship between prolonged remission, higher risk of MetS, and development of NAFLD [ 21 ].…”
Section: Nafld In Ibd Patients With “Metabolic Syndrome Profile”mentioning
confidence: 99%
“…More recent publications confirm most of these data and attribute them to the changed metabolic profile of IBD patients in recent years. Thanks to new biologic drugs, these patients have gone from being malnourished to being obesity/overweight in up to a third of cases[ 27 , 32 , 33 ].…”
Section: Nafld and Ibdmentioning
confidence: 99%
“…Неалкогольная жировая болезнь печени (НАЖБП) -самый частый вариант патологии печени при ВЗК: до 55% случаев выявляют при ЯК, до 39% -при БК [7]. К традиционным факторам риска НАЖБП при ВЗК относят мужской пол, возраст, диету с высокой калорийностью и большой долей жиров [8][9][10]. В качестве триггеров также рассматривают синдром мальабсорбции с дефицитом белка, изменения микробиоты и гепатотоксические эффекты базисной терапии [11,12].…”
Section: клинические исследованияunclassified